Analysis of the Use of Halal Labels, Celebrity Endorsers, and Product Knowledge and their Effects on Cosmetic Product Purchase Decisions - Yusnidar Yusnidar (Almana : Jurnal Manajemen dan Bisnis, 2022)
Technology and Innovation makes a large number of Muslims in Indonesia an opportunity by presenting halal cosmetic products. In the current era of modern technology, celebrity endorsers have become a means of promotion that supports the public interest in products that have been offered on social media. This study aims to analyze the effect of halal labels on purchasing decisions for cosmetic products, analyze how much influence celebrity endorsers have on purchasing decisions for cosmetic products, analyze how much influence product knowledge has on purchasing decisions for cosmetic products, and analyze how much influence halal labels, celebrity endorsers and product knowledge have. on purchasing decisions for cosmetic products. A total of 96 respondents used multiple correlation research methods. The results of this study indicate that halal labels have a positive and significant influence on cosmetic purchasing decisions, celebrity endorsers have a positive and significant influence on cosmetic purchasing decisions, product knowledge has a positive and significant influence on cosmetic purchasing decisions, halal labels, celebrity endorsers and product knowledge have a positive and significant impact on cosmetic purchasing decisions. positive and significant influence on cosmetic purchasing decisions.